Effectiveness and cost of hepatitis C virus cryoglobulinaemia vasculitis treatment: From interferon‐based to direct‐acting antivirals era. (29th May 2017) - Cacoub, Patrice; Vautier, Mathieu; Desbois, Anne Claire; Lafuma, Antoine; Saadoun, David
Abstract: Background: The net benefits of new hepatitis C virus (HCV) direct‐acting antiviral drugs (DAA) in patients with cryoglobulinaemia vasculitis (CryoVas) are unknown. Objective: To analyse the effectiveness and cost of all treatments used for HCV‐CryoVas in the DAA vs pre‐DAA era. Methods: A chart review of all HCV‐CryoVas patients who received antivirals from 1993 to 2016 in a tertiary centre was performed. Treatment effectiveness was analysed for clinical, immunological and virological responses. Cost analyses included anti‐HCV treatments, non‐antiviral drugs, plasmapheresis, dialysis and hospitalizations. We compared main data in the pre‐DAA vs DAA period. Results: About 201 HCV‐CryoVas patients were included (women, 53.2%; mean age, 59.2 years; Metavir score F3‐F4, 36.7%; genotype 1, 64.2%). Patients in the DAA era (n=27) compared to those in the pre‐DAA era (n=174) showed higher rates of clinical (96.3% vs. 78.6%), immunological (89.5% vs. 77.1%), and sustained virological response (75.0% vs. 42.8%). Death rate was 14.8% vs. 24.4% respectively. In the DAA compared to pre‐DAA era, mean cost of anti‐HCV drugs increased from 11 855 to 57 632 € while mean CryoVas‐related cost decreased for both hospitalizations (from 33 510 to 21 347€) and non‐antiviral treatments (from 17 347 to 11 397€). Conclusion: Improved antiviral efficacy of HCV drugs in the DAA era led to increased clinical and immunological efficacy and a lower death rate. Use of DAAs was associated to higher costs for HCV drugs while costs related to both hospitalizations and non‐antiviral treatments decreased.